Health literacy breakthroughs in research and practice (Medical Information Science Reference, 2017)
"This book examines the latest advances in providing and helping patients and medical professionals to understand basic health information and the services that are most appropriate. Including innovative studies on interactive health information, health communication, and health education"--Provided by publisher.